RESEARCH OF THE RELIABILITY OF ROTARY OVENS OF A BAKERY FACTORY AND THE DEVELOPMENT OF MECHATRONIC SYSTEMS TO PROTECT THEM AGAINST ACCIDENTS - KHOROLSKY, VALENTYN; KORENETS, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article updates the issues of research into the performance of rotary kilns during the period of gas and electricity supply restrictions. An algorithm for evaluating the reliability of rotary kilns during periods of gas supply restrictions due to the inclusion of backup sources has been developed. It has been proven that the quality indicators of bakery products depend on the reliable operation of technological equipment; level of knowledge of technologists-operators; the level of information and algorithmic support; intellectual and informational decision-making support of the person who makes operational decisions. The main role in this case will be played by the level of intellectualization of equipment management during periods of energy supply restrictions and fan power outages, timely recognition of emergency situations and accidents, and preventive maintenance of bakery production equipment by personnel. The task of operators and control systems during the operation of the rotary oven is to create and maintain normative values of the bread baking temperature during periods of electricity and gas supply restrictions and to recognize emergency situations and accidents in time with the process. As a result, an automated control system for a rotary kiln with a built-in mechatronic system for evaluating the reliability of equipment and monitoring the state of energy factors was developed and proposed, which was designed taking into account local conditions and intended for implementation at bread factories of the Dnieper economic region under martial law. The main features of the developed system are the use of reliability provisions of complex systems, algorithms and monitoring systems with the recognition of accidents that occur during the operation of rotary kilns. The main attention is paid to the development of an expert control system for supplying rotary kilns with energy carriers (gas, electricity) and their backup.